Frailty and postoperative complications in older Chinese adults undergoing major thoracic and abdominal surgery - Han B (Dove Medical Press, 2019)
Binru Han, Qiuping Li, Xi ChenDepartment of Nursing, Xuanwu Hospital, Capital Medical University, Beijing, People’s Republic of ChinaPurpose: To determine the association between frailty and postoperative complications in elderly Chinese patients and to determine whether addition of frailty assessment improves the predictive ability of the American Society of Anesthesiologists (ASA) score, Physiological and Operative Severity Score for the Enumeration of Mortality and Morbidity (POSSUM), and Estimation of Physiologic Ability and Surgical Stress (E-PASS) score.Patients and methods: A prospective cohort study was conducted in a tertiary hospital. Elderly patients undergoing major thoracic or abdominal surgery were included. Frailty phenotype and ASA, POSSUM, and E-PASS scores were assessed. Demographic, preoperative, and surgical variables were extracted from medical records. Primary outcome measure was in-hospital Clavien-Dindo ≥ grade II complications. Multiple logistic regression was used to examine the association between frailty and complications. Receiver operating characteristic curves were used to explore the predictive ability of frailty.Results: Prevalence of frailty was 26.12%. Significant differences were observed between the frail and non-frail groups with respect to age, Activities of Daily Living, Charlson Comorbidity Index, respiratory function, presence of malignancy, serum albumin, prealbumin, and hemoglobin levels (P<0.05). ASA, POSSUM, and E-PASS scores were higher in the frail group. After adjusting for all covariates, frailty was significantly associated with postoperative complications in hospital [odds ratio: 16.59, 95% CI: 4.56–60.40, P<0.001]. The area under the curve (AUC) for frailty was 0.762 (95% CI: 0.703–0.814). The AUC for ASA, POSSUM, and E-PASS for prediction of complications was 0.751 (95% CI: 0.692–0.804), 0.762 (95% CI: 0.704–0.814), and 0.824 (95% CI: 0.771–0.870), respectively. Addition of frailty assessment increased the AUC to 0.858 (95% CI: 0.808–0.899), 0.842 (95% CI: 0.790–0.885), and 0.854 (95% CI: 0.803–0.896), respectively.Conclusion: Frailty is an effective predictor of postoperative complications in elderly Chinese patients undergoing major thoracic and abdominal surgery. Frailty assessment can improve the predictive ability of current surgical risk assessment tools. Frailty phenotype should be considered perioperatively. Frailty assessment could also expand the scope for nurses to evaluate patients for safety management.Keywords: frailty assessment, risk assessment tool, surgery, postoperative complication